2018
DOI: 10.1111/dgd.12576
|View full text |Cite
|
Sign up to set email alerts
|

Parallel transcriptome evolution in stream threespine sticklebacks

Abstract: Natural selection can cause similar phenotypic evolution in phylogenetically independent lineages inhabiting similar environments. Compared to morphological, behavioral, and physiological traits, little is known about the parallel evolution of transcriptome. Furthermore, the relative contribution of cis‐ and trans‐regulatory changes to parallel transcriptome evolution largely remains unclear. The threespine stickleback fish (Gasterosteus aculeatus) is a great model for studying parallel evolution because its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 86 publications
3
15
0
Order By: Relevance
“…The levels of enrichment of clinal polymorphisms observed here are larger than those observed for other functional categories in Drosophila (Machado et al 2016) and other species (Ye et al 2013;Mack et al 2018), suggesting that SNPs underlying clinal adaptation are more likely to be eQTLs than other categories. This finding agrees with growing literature showing evidence that spatial differentiation at eQTLs contributes to local adaptation across various taxa (Fraser 2013;Gould et al 2017;Kitano et al 2018;Mack et al 2018;Phifer-Rixey et al 2018;Colicchio et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The levels of enrichment of clinal polymorphisms observed here are larger than those observed for other functional categories in Drosophila (Machado et al 2016) and other species (Ye et al 2013;Mack et al 2018), suggesting that SNPs underlying clinal adaptation are more likely to be eQTLs than other categories. This finding agrees with growing literature showing evidence that spatial differentiation at eQTLs contributes to local adaptation across various taxa (Fraser 2013;Gould et al 2017;Kitano et al 2018;Mack et al 2018;Phifer-Rixey et al 2018;Colicchio et al 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The level of parallelism for gene expression abundance changes varies across study systems. In some taxa and natural conditions, significantly more genes show parallel changes (repeatedly up- or down-regulated in one ecotype relative to the other among independent population pairs) than anti-directional changes (Zhao et al 2015; Hart et al 2018; Kitano et al 2018; McGirr and Martin. 2018).…”
Section: Introductionmentioning
confidence: 99%
“…An ecologically important fish species of interest for epigenetic studies in wild populations is threespine stickleback (Gasterosteus aculeatus), as it has been widely used as a model system to investigate the genetic and non-genetic basis of adaptation to novels environments (Shama and Wegner, 2014;Shama et al, 2016;Shama, 2017;Heckwolf et al, 2018;Metzger and Schulte, 2018;Kitano et al, 2019). After the last glaciation, marine stickleback colonized freshwater habitats of the north temperate zone, leading to local adaptation of populations that exhibit different phenotypes based on, for example, behavior, armor plate number, body shape, and gene expression plasticity (Kitano et al, 2019). Furthermore, whole genome sequence comparisons between freshwater and marine individuals revealed that differential gene expression contributed more to adaptive evolution than protein sequence evolution (Kitano et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…After the last glaciation, marine stickleback colonized freshwater habitats of the north temperate zone, leading to local adaptation of populations that exhibit different phenotypes based on, for example, behavior, armor plate number, body shape, and gene expression plasticity (Kitano et al, 2019). Furthermore, whole genome sequence comparisons between freshwater and marine individuals revealed that differential gene expression contributed more to adaptive evolution than protein sequence evolution (Kitano et al, 2019). This, in combination with the ability to study the evolution of sex chromosome systems make stickleback an ideal candidate to elucidate the role of epigenetic mechanisms in reproduction, development, and adaptation in fishes (Figure 1).…”
Section: Introductionmentioning
confidence: 99%